Political Empowerment of Arab Women: The Iraqi Model - Lecturer. Dr. SAHAR TAREQ MAHMOOD AL-RAHEEM (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Political Empowerment of Arab Women: The Iraqi Model